EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA GORONTALO TAHUN 2016-2018 - Chandra, Cherry Agustine; Sabijono, Harijanto; Runtu, Treesje (Universitas Sam Ratulangi, 2020)
The Rural and Urban Land and Building Tax (PBB-P2) is a central tax which is handed over to the local government so that it becomes a local tax. PBB-P2 is expected to be able to contribute to the receptionof special regions. The purpose of this study is to calculate the acceptance and acceptance of PBB-P2 revenue towards increasing PAD revenue in Gorontalo City. The research method uses a qualitative type with Gorontalo City government as the object of research. Data collection techniques with interviews and documentation. The results showed that PBB-P2 revenues in Gorontalo City amounted to 88,86% in 2016, 79,80% in 2017, and 81,24% in 2018, and receipt of PBB-P2 revenue towards PAD 2016 was 2,89%, in 2017 it was 2,80%, and 2018 it was 3,05%.